2020
DOI: 10.1017/qua.2020.62
|View full text |Cite
|
Sign up to set email alerts
|

In-phase and out-of-phase behavior of the East Asian summer and winter monsoons recorded in the South Yellow Sea sediment over the past 9.5 ka

Abstract: The variability of the East Asian monsoon (EAM) during the Holocene exhibits significant regional response, and its evolution needs further discussion. A well-dated, high-resolution sea-surface temperature record based on long-chain unsaturated alkenones, grain-size data, and clay mineral assemblages from the South Yellow Sea sediment is presented to investigate the sedimentary provenance and reconstruct the EAM over the past 9.5 ka. The results show that the sediments are most likely supplied by the Huanghe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
(228 reference statements)
0
4
0
Order By: Relevance
“…Here, we interpret δ 13 C and Mg/Ca variability as primarily driven by prior calcite precipitation (PCP), a process commonly associated with co-variance between δ 13 C and Mg/Ca. When PCP occurs, 12 CO 2 is preferentially degassed and magnesium, as well as other trace elements with partition coefficients smaller than 1, is preferentially excluded from calcite precipitated in the epikarst or on stalactite surfaces, leading to increased δ 13 C and Mg/Ca in the remaining solution which ultimately feeds the stalagmite 28 . PCP is enhanced during dry periods, as has been shown by previous studies [29][30][31][32] .…”
Section: Multiproxy Records Of Southeast Asian Monsoon Precipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we interpret δ 13 C and Mg/Ca variability as primarily driven by prior calcite precipitation (PCP), a process commonly associated with co-variance between δ 13 C and Mg/Ca. When PCP occurs, 12 CO 2 is preferentially degassed and magnesium, as well as other trace elements with partition coefficients smaller than 1, is preferentially excluded from calcite precipitated in the epikarst or on stalactite surfaces, leading to increased δ 13 C and Mg/Ca in the remaining solution which ultimately feeds the stalagmite 28 . PCP is enhanced during dry periods, as has been shown by previous studies [29][30][31][32] .…”
Section: Multiproxy Records Of Southeast Asian Monsoon Precipitationmentioning
confidence: 99%
“…Modern meteorological observations show a strong coupling between the Asian winter and summer monsoons 2 . However, while several paleoclimate studies have found a positive correlation over glacial-interglacial timescales [3][4][5] , there is still no consensus on whether these two seasonal monsoon systems were similarly linked during the Holocene [6][7][8][9][10][11][12][13][14][15] . Several studies tried to address the co-evolution of the winter and summer monsoon in Southeast Asia over the Holocene, arguing for 16 and against 10,17,18 an inverse correlation, while others found that this relation changes depending on time scales 13,19 .…”
mentioning
confidence: 99%
“…Quaternary sediments have a mean thickness of ∼224 m (Gao et al., 2020; Qin et al., 1989). Since the Quaternary, the sedimentary sequences of the SYS shelf have been strongly influenced by sea‐level fluctuations represented by alternating marine and terrestrial deposits (Mei et al., 2016; L. Wang, Li, Liu, et al., 2021; L. Wang, Li, Wang, et al., 2021).…”
Section: Oceanographic and Geologic Settingmentioning
confidence: 99%
“…Yet the impacts of EAWM variability on marine biota are poorly understood. The Yellow Sea (YS) has been regarded as an ideal location to study the evolution of the EAWM, as it is sensitive to climate change, and its environment is strongly influenced by the EAWM (Hao et al., 2017; L. Wang, Li, Liu, et al., 2021; L. Wang, Li, Wang, et al., 2021). Furthermore, the YS is also the southern end of the distribution of some circumpolar species in the northwestern (NW) Pacific Ocean (J. Y. Liu, 2013; R. Y. Liu, 2011).…”
Section: Introductionmentioning
confidence: 99%